Rights of Children of Mixed Marriages to Inheritance from Deceased Parents - Wahid Yaurwarin (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Mixed marriages have penetrated all corners of the country and all levels of society. This is due to the influence of globalization, information, economics, and transformation, which have increased human mobility through migration from one country to another. This causes individuals to meet and communicate with various ethnic groups with different cultures, religions, and customs. According to Article 57, a mixed marriage is a marriage between two people in Indonesia subject to different laws due to differences in citizenship, with one party holding Indonesian citizenship. One of the issues that often poses an obstacle for people entering into mixed marriages, both domestically and internationally, is the issue of legal protection if one or both parents die during the marriage, resulting in the distribution of inheritance. The method used is normative juridical. According to Soerjono Soekanto, the normative juridical approach is legal research conducted by examining library materials or secondary data as a basis for research by exploring regulations and literature related to the problem under study. The conclusion of this paper is that the rights of children from mixed marriages to the inheritance of deceased parents are, in principle, still recognized and protected by law. Children have the same legal standing as heirs, as long as their civil relationship is valid according to applicable laws and regulations. However, in practice, issues often arise related to differences in legal systems (national and foreign), citizenship, and conflicts over inheritance laws that can affect the distribution of inheritance.